2021
DOI: 10.1126/sciimmunol.abg5003
|View full text |Cite
|
Sign up to set email alerts
|

Pax5 regulates B cell immunity by promoting PI3K signaling via PTEN down-regulation

Abstract: The transcription factor Pax5 controls B cell development, but its role in mature B cells is largely enigmatic. Here, we demonstrated that the loss of Pax5 by conditional mutagenesis in peripheral B lymphocytes led to the strong reduction of B-1a, marginal zone (MZ), and germinal center (GC) B cells as well as plasma cells. Follicular (FO) B cells tolerated the loss of Pax5 but had a shortened half-life. The Pax5-deficient FO B cells failed to proliferate upon B cell receptor or Toll-like receptor stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 90 publications
1
28
0
Order By: Relevance
“…Immunization with the T cell–dependent antigen NP-keyhole limpet hemocyanin (NP-KLH) in the adjuvant alum demonstrated that no germinal center (GC) B cells were generated in the spleen of Pax5 R31Q/− mice on day 14 after immunization ( Fig. 4 E ), similar to the absence of GC B cells in response to conditional Pax5 deletion in mature B cells ( Calderón et al, 2021 ). Consequently, NP-specific plasma cells were strongly reduced in the spleen of Pax5 R31Q/− mice ( Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Immunization with the T cell–dependent antigen NP-keyhole limpet hemocyanin (NP-KLH) in the adjuvant alum demonstrated that no germinal center (GC) B cells were generated in the spleen of Pax5 R31Q/− mice on day 14 after immunization ( Fig. 4 E ), similar to the absence of GC B cells in response to conditional Pax5 deletion in mature B cells ( Calderón et al, 2021 ). Consequently, NP-specific plasma cells were strongly reduced in the spleen of Pax5 R31Q/− mice ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…PAX5 is well known for its role in B cell immunity ( Calderón et al, 2021 ; Horcher et al, 2001 ; Nutt et al, 1999 ) and its function as a haploinsufficient tumor suppressor gene in B cell acute lymphoblastic leukemia ( Gu et al, 2019 ; Mullighan et al, 2007 ). Here, we identified new functions of Pax5 in controlling cerebellar development and the neurogenesis of GABAergic midbrain neurons and demonstrated a causative involvement of PAX5 deficiency in ASD etiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deletion of PTEN can increase the threshold of neutrophils’ response to chemokines and reduce neutrophil-mediated inflammation to a certain extent ( Billadeau, 2008 ). In addition, PTEN inhibits the differentiation of B cells into plasma cells by regulating PI3K Signal transduction ( Calderón et al, 2021 ). Zhu et al (2021) found that miR-520b targeting PTEN promoted the polarization of M0 macrophages toward M2 in breast cancer.…”
Section: Discussionmentioning
confidence: 99%